2006
DOI: 10.1016/j.ijnonlinmec.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear behaviour of free-edge shallow spherical shells: Effect of the geometry

Abstract: International audienceNon-linear vibrations of free-edge shallow spherical shells are investigated, in order to predict the trend of non-linearity (hardening/softening behaviour) for each mode of the shell, as a function of its geometry. The analog for thin shallow shells of von Kármán's theory for large deflection of plates is used. The main difficulty in predicting the trend of non-linearity relies in the truncation used for the analysis of the partial differential equations (PDEs) of motion. Here, non-linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 43 publications
2
50
0
1
Order By: Relevance
“…• Due to the curvature of some SDOF solutions, the cubic terms in (6), neglected in the model, should be taken into account, as this feature is a characteristic of a cubic nonlinearity of the softening type [17,18]. The correction brought by the cubic terms is of the same order of magnitude as the nonresonant terms that couple the three involved modes to the other modes of the system.…”
Section: Resultsmentioning
confidence: 99%
“…• Due to the curvature of some SDOF solutions, the cubic terms in (6), neglected in the model, should be taken into account, as this feature is a characteristic of a cubic nonlinearity of the softening type [17,18]. The correction brought by the cubic terms is of the same order of magnitude as the nonresonant terms that couple the three involved modes to the other modes of the system.…”
Section: Resultsmentioning
confidence: 99%
“…motion [42,43,44]. This is also why in Table 1, eigenmodes are presented by increasing order of the frequencies, except the last two (axisymmetric), which have significantly larger eigenfrequencies: asymmetric modes in between have not been reported in the table.…”
Section: Numerical Detailsmentioning
confidence: 86%
“…When a curvature is present, the type of behaviour (hardening or softening) depends on the balance between quadratic and cubic terms. The transition between these two cases has been studied by Fletcher, for a single mode of simple rods systems, by Thomas et al [13], and, more exhaustively, by Touzé and Thomas for shallow spherical shells [14]. In this latter paper, it is shown that increasing the curvature leads to changing the behaviour from hardening to softening.…”
Section: Pitch Glidementioning
confidence: 89%